PENGARUH MOTIVASI, KEPUASAN KERJA, PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN - HANDINATA, GUNTUR PUTRA; Tjahjadi, Karel (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
In achieving the company's goals some problems or gaps must be faced effectively, companies need planning to solve these problems, one of them is by paying attention to human resources. Based on the results, a brief meeting with the manager at PT. X, there is a decrease in performance appraisal in 2019 – 2021 and there is a research gap that examines motivation, job satisfaction, human resource development on employee performance. The purpose of this study is to determine whether there is an influence between motivation, job satisfaction, and human resource development on employee performance. This study uses a population of 75 respondents and using a sample of 75 in the form of a saturated sample. The data given to the respondents used a Likert scale measurement. In this study, researchers used multiple regression as an analytical method. The results of this study showed motivation has a positive effect on employee performance.